(untitled) (Itinera, 2022)
The issue of color in photography constitutes one of those issues that have characterized and enlivened, especially since the post-war period, the debate around a fundamental aspect of the language of photography. I have limited myself to just hinting at the more dated aspects of this discussion (e.g., whether color photography is to be considered authentic photography in a vision that identifies its chromatic language with pure black and white) while trying to outline a reflection that is more attentive to current issues. In particular – the subtitle of this essay pinpoints this aspect – I have inserted the topic of color in the phase of transformation that photography is undergoing. Specifically, photography is considered and practiced not only in a documentary and mimetic function, but also as a multifaceted tool strongly linked to the experiences of the other visual arts. From this perspective, I have added my personal experience as a photographer to some historicized practices, of which I give a few examples.